THE EFFECT OF LEVERAGE AND SALES GROWTH ON FINANCIAL DISTRESS WITH PROFITABILITY AS A MEDIATOR - I Putu Artha Pratama Gunawan; Putu Ery Setiawan (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Financial distress is a condition characterized by a decline in a company's financial performance prior to bankruptcy. This study aims to examine the effect of leverage and sales growth on financial distress with profitability as a mediating variable in metal goods and related sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample consists of 16 companies determined using the purposive sampling method. The data analysis techniques employed include descriptive analysis and inferential analysis, which consist of path analysis, Sobel test, and t-test. The results indicate that leverage has a significant negative effect on financial distress, while sales growth has no effect on financial distress. Profitability has a significant positive effect on financial distress, and leverage has a significant negative effect on profitability, whereas sales growth has a significant positive effect on profitability. Furthermore, profitability is proven to mediate the effect of leverage and sales growth on financial distress.